FAKTOR-FAKTOR YANG MEMENGARUHI KEBAHAGIAAN DI TEMPAT KERJA PADA PT XYZ TAHUN 2023 - Carlos Piero Martua (2024)
Relationships with other workers and stress at work can be overcome when workers are happy because workers' behavior is better at handling problems, so productivity increases. This study aim is to analyze the factors influencing workplace happiness at PT XYZ in 2023. This research applied a cross-sectional study design in Jakarta, Indonesia, from November to December 2023. The sampling method was disproportionate stratified sampling with a sample of 100 male workers of manufacturing companies. Primary data are collected using the Indonesian Version of Happiness at Work Scale, job inspiration, relationship, leadership, and quality of work life questionnaire, which are analyzed using a logistic regression test. The results showed that 51 out of 100 respondents (51%) experienced low levels of workplace happiness. The variables associated with workplace happiness were relationship (p-value= 0.014) and leadership (p-value= 0.029), but job inspiration (p-value= 0.152) and quality of work life (p-value= 0.246) are not associated. The factors included in the multivariate model were worker status, job inspiration, relationship, leadership, and quality of work life. The most dominant factor influencing workplace happiness is relationship (POR= 5.386). Companies should conduct periodic online surveys for some health issues and provide conflict management training for both managers and workers.